2012
DOI: 10.3892/etm.2012.715
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of tumor suppressor genes in ovarian cancer

Abstract: Aberrant methylation of gene promoter regions is one of the mechanisms for inactivation of tumor suppressor genes in human malignancies. In this study, the methylation pattern of 24 tumor suppressor genes was analyzed in 75 samples of ovarian cancer using the methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) assay. Of the 24 tumor suppressor genes examined, aberrant methylation was observed in 17. The three most frequently methylated genes were CDKN2B, CDH13 and RASSF1, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Previous studies have indicated that the use of enzymes or a combination of acid hydrolysis can significantly reduce the viscosity of mucus (14,15). The results of the present study demonstrated that experimental dosages of 0.6 and 0.4 mg/ml MMC can decrease the level of sialic acid in the urine and the number of mature goblet cells, with the effect dose-dependent.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have indicated that the use of enzymes or a combination of acid hydrolysis can significantly reduce the viscosity of mucus (14,15). The results of the present study demonstrated that experimental dosages of 0.6 and 0.4 mg/ml MMC can decrease the level of sialic acid in the urine and the number of mature goblet cells, with the effect dose-dependent.…”
Section: Discussionsupporting
confidence: 63%
“…Two alternatively spliced transcript variants of this gene, which encode distinct proteins, have been reported (provided by RefSeq, Jul 2008). Methylation of CDKN2B has been found in several cancer types including laryngeal squamous cell carcinoma, acute myeloid leukemia, and in ovarian cancer, where the presence of methylation in the CDKN2B gene was present mainly in clear cell carcinoma [34][35][36] . MUS81 (Structure-Specific Endonuclease Subunit) is a protein coding gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no correlations between the methylation levels of BRCA1 and ER that were determined by MSP method and the clinical and pathological parameters of tumors were observed in 215 ovarian cancer patients (Wiley et al, 2006). Moreover, methylation status of BRCA1 and ER determined by MS-MLPA method and that of BRCA1 and RASSF1A determined by head loop PCR showed no association with tumor stages in 75 and 80 ovarian tumors, respectively (Montavon et al, 2012;Ozdemir et al, 2012). It is notable that the correlation between methylation of these genes and clinic-pathological tumor has been reported at the late stage (FIGO III/IV) of ovarian tumors whereas almost all of the examined specimens in our study were in the early stage (FIGO I/II) (Teodoridis et al, 2005;BonDurant et al, 2011).…”
Section: Sequencing Msp Products Representative To Brca1 Rassf1a Andmentioning
confidence: 97%